Not dead things : the dissemination of popular print in England and Wales, Italy, and the Low Countries, 1500-1820 - Harms, Roeland, 1979-; Raymond, Joad; Salman, Jeroen (Library of the written word, 2013)
This collection explores the surprising ways by which cheap print moved across Europe, focussing on Italy, the Netherlands and Britain. Looking at pedlars, commerce and communication, it presents a model of textual dissemination and the material and economic premises of European landscapes of print.